“Representation Condition Political 20th Century Java : An Analysis Fiber Speech Hard” - Dewa Alfaquin Faturangga, S.Hum; Yahya Abu Zaky; Raihani Raya Budianto (2025)
Serat Wicara Keras is one of the most renowned literary works, as it contains various lessons, including history, social values, culture, politics, religion, and philosophy. This manuscript was later reproduced in the 20th century by Yasadipura III, also known as R. Ng. Sastrawikrama, as a depiction of social criticism and the author’s anger toward the ruling leaders or government. However, an important question arises regarding the reason behind the writing of this manuscript. What political conditions served as the main trigger for the creation of Serat Wicara Keras. What images and portrayals emerged from its composition. This study employs a descriptive qualitative method with a literary hermeneutic approach, further supported by Shoshana Felman’s Testimony theory, to interpret the events depicted in Yasadipura II’s 1820 work Serat Wicara Keras. The analysis reveals political influences spanning from the aftermath of the Java War to the independence of Indonesia, which shaped the political landscape of Java. It also highlights the role of post-independence Indonesian activists in safeguarding national sovereignty amid various internal conflicts, extending into the Reform Era. This represents how the political climate in Indonesia evolved and the extent to which the content of Serat Wicara Keras reflected the realities of its time.